(untitled) (مجلة التربوي, 2025)
Educational songs are a widely used pedagogical tool in early childhood settings, yet their impact on young children's learning and development is not fully understood. This paper aims to synthesize the existing research on the role of English educational songs in the nursery classroom and explore their multifaceted benefits. This paper explores the benefits of incorporating English educational songs into the curriculum for young pupils at the nursery stage in Libya. An open-ended interview was conducted with 7 Libyan EFL teachers to get the wanted data. The key findings from this paper appealed that the English educational songs have a great effect on children English learning and proposes practical strategies for effectively integrating educational songs into the nursery classroom. Children ability to speak English improved and they gain more vocabulary.